2008
DOI: 10.1002/jpln.200700054
|View full text |Cite
|
Sign up to set email alerts
|

Physical carbon‐sequestration mechanisms under special consideration of soil wettability

Abstract: The protective impact of aggregation on microbial degradation through separation has been described frequently, especially for biotically formed aggregates. However, to date little information exists on the effects of organic‐matter (OM) quantity and OM quality on physical protection, i.e., reduced degradability by microorganisms caused by physical factors. In the present paper, we hypothesize that soil wettability, which is significantly influenced by OM, may act as a key factor for OM stabilization as it con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 77 publications
2
83
0
2
Order By: Relevance
“…Hydrophilic tendencies maintain a water film within aggregate complexes and thus contribute to transmission of water and promote increased wetting. The pore space in soil is also modified by the SOC composition; the hydrophobicity of some elements of SOC act to selectively block soil pores (Schulten and Schnitzer 1997;Bachmann et al 2008). From the orientation of carbon molecules, small changes in SOC within aggregates can alter the flow of water between and within molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrophilic tendencies maintain a water film within aggregate complexes and thus contribute to transmission of water and promote increased wetting. The pore space in soil is also modified by the SOC composition; the hydrophobicity of some elements of SOC act to selectively block soil pores (Schulten and Schnitzer 1997;Bachmann et al 2008). From the orientation of carbon molecules, small changes in SOC within aggregates can alter the flow of water between and within molecules.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not as obvious to understand the persistent long-term relationship among SOC, texture, and time-averaged SWC, which would include feedback between the variables. The SOC is also associated with changes in hydrophilic versus hydrophobic attractions to water on the surface of aggregates (Bachmann et al 2008). Increased hydrophobicity from SOC within aggregates is proposed to regulate water entry into pores (Schulten and Schnitzer 1997;Bachmann et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SWR has also been reported to reduce soil microbial activity and it has been considered as one of the factors protecting SOM from microbial decomposition by separation of the microorganisms from their food and water sources (Piccolo and Mbagwu, 1999;Piccolo et al, 1999;Bachmann et al, 2008). Goebel et al (2007) demonstrated that SWR affects the distribution and continuity of the liquid phase in the soil matrix and therefore restricts the accessibility of SOM and the availability of water, O 2 and nutrients to the microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, research of the last decades revealed also some negative effects associated with the amount and composition of SOM like soil water repellency (WR), which may lead to adverse effects with respect to soil hydraulic functions. Bachmann et al (2008) showed that the availability and distribution of water in the soil matrix depends on soil particle wettability. WR occurs in soils of different texture, land use and under a variety of climatic conditions (DeBano, 1981;Doerr et al, 2000;Woche et al, 2005).…”
Section: Introductionmentioning
confidence: 99%